Peroxiredoxin 6 as a Unique Member of the Peroxiredoxin Family - Fisher, Aron B. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The peroxiredoxin family was discovered approximately 30 years ago and is now recognized as one of the most important families of enzymes related to antioxidant defense and cellular signaling. Peroxiredoxin 6 shares the basic enzymatic functions that characterize this family, but also exhibits several unique and crucial activities. These include the ability to reduce phospholipid hydroperoxides, phospholipase A2 activity, and an acyl transferase activity that is important in phospholipid remodeling. This book describes the available models for investigating the unique functions of PRDX6 and its role in normal physiological function, as well its roles in the pathophysiology of diseases including cancer, diseases of the eye, and male fertility.